2012
DOI: 10.1017/s0025315412000690
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the White Sea colonial hydroidDynamena pumilaand microorganisms

Abstract: Marine sessile invertebrates with outer skeleton constitute additional substrate for a diverse group of epibiotic organisms. Colonial hydroids are no exception. Large numbers of motile and sessile organisms use hydroid colonies covered with chitinous perisarc for permanent or temporal attachment. Such epibiotic associations between colonial hydroids and microorganisms are poorly studied and mostly known for subtropical regions. There are no data about the development of such epibiotic association and type of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A previous research reported that surface chitin-containing structures of the hydroid Aglaophenia octodonta (Stabili et al , 2006) are heavily colonized by luminous bacteria belonging to the genus Vibrio. Moreover, a recent study by Gorelova et al (2010) demonstrated a feeding activity of bacteria on the surface of the hydrozoans Dynamena pumila and Gonothyrea loveni , showing micro-perforations within the perisarc containing the microrganisms, presumably due to chitin lysis. In the present study, the occurrence of luminous bacteria in the investigated hydrozoan species could be related to differences in the chitin localization as well as presence or absence of the perisarc.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous research reported that surface chitin-containing structures of the hydroid Aglaophenia octodonta (Stabili et al , 2006) are heavily colonized by luminous bacteria belonging to the genus Vibrio. Moreover, a recent study by Gorelova et al (2010) demonstrated a feeding activity of bacteria on the surface of the hydrozoans Dynamena pumila and Gonothyrea loveni , showing micro-perforations within the perisarc containing the microrganisms, presumably due to chitin lysis. In the present study, the occurrence of luminous bacteria in the investigated hydrozoan species could be related to differences in the chitin localization as well as presence or absence of the perisarc.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, Bavestrello et al (1996, 2008), Siqueiros-Beltrones et al (2001), Di Camillo et al (2005, 2008) and Romagnoli et al (2007) described epibiotic bacteria, diatoms, and foraminiferans from both Mediterranean and tropical hydroids. Moreover, Gorelova et al (2010) observed by electron microscopy that the epibiotic community of the hydroid perisarc of Dynamena pumila and Gonothyraea loveni consisted of different microalgae and bacteria. These findings suggest many interactions between the hydroids and epibiotic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Various cyanobacterial strains form associations with sponges, hydroids, corals, dinoflagellates, radiolarians, and tintinnids [18]. Mostly, the studies of cyanobacterial associations are limited to subtropical and tropical marine water systems.…”
Section: Introductionmentioning
confidence: 99%